The holy history of mankind and other writings - Hess, Moses, 1812-1875 (Cambridge texts in the history of political thought., 2004)
Moses Hess is a major figure in the development of both early communist and Zionist thought. The Holy History of Mankind appeared in 1837, and was the first book-length socialist tract to appear in Germany, representing an unusual synthesis of Judaism and Christianity that showed the considerable influence upon Hess of Spinoza, Herder and Hegel. In due course many of Hess's ideas would find their way into the work of Karl Marx, and into subsequent socialist thought. The distinguished political scientist Shlomo Avineri provides the first full English translation of this text, along with new renditions of Socialism and Communism, A Communist Credo; and The Consequences of a Future Revolution of the Proletariat. All of the usual reader-friendly series features are provided, including a chronology, concise introduction and notes for further reading, in a work of special relevance to students of politics, modern European history, and the history of Zionism.